2015
DOI: 10.1371/journal.pone.0122065
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dedifferentiating Human Mature Adipocytes from the Visceral and Subcutaneous Fat Compartments: Fibroblast-Activation Protein Alpha and Dipeptidyl Peptidase 4 as Major Components of Matrix Remodeling

Abstract: Mature adipocytes can reverse their phenotype to become fibroblast-like cells. This is achieved by ceiling culture and the resulting cells, called dedifferentiated fat (DFAT) cells, are multipotent. Beyond the potential value of these cells for regenerative medicine, the dedifferentiation process itself raises many questions about cellular plasticity and the pathways implicated in cell behavior. This work has been performed with the objective of obtaining new information on adipocyte dedifferentiation, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 45 publications
4
45
0
Order By: Relevance
“…In tumorigenic cells and wounds, this heteromeric complex is localised on the advancing portion of invadopodia that is believed to play an important role in tumour invasion, spreading of metastasis, angiogenesis and wound-healing, respectively [6,7,13,22]. Thus, to identify it as a pharmaceutical target, the expression of FAP has been investigated as potential biomarker in several types of cancers [6,7,13,[23][24][25]. Interestingly, it was shown that stromal FAP is more prominent in early-stage colorectal cancer and smaller tumour xenografts, with increased expression of FAP being an adverse prognostic indicator in patients with advanced metastatic disease [26].…”
Section: Dpp4 Gene Familymentioning
confidence: 99%
“…In tumorigenic cells and wounds, this heteromeric complex is localised on the advancing portion of invadopodia that is believed to play an important role in tumour invasion, spreading of metastasis, angiogenesis and wound-healing, respectively [6,7,13,22]. Thus, to identify it as a pharmaceutical target, the expression of FAP has been investigated as potential biomarker in several types of cancers [6,7,13,[23][24][25]. Interestingly, it was shown that stromal FAP is more prominent in early-stage colorectal cancer and smaller tumour xenografts, with increased expression of FAP being an adverse prognostic indicator in patients with advanced metastatic disease [26].…”
Section: Dpp4 Gene Familymentioning
confidence: 99%
“…However, in vitro studies have shown that mature adipocytes are able to return to a more primitive phenotype when they are subjected to ceiling culture [1]. In previous studies, we have shown that the dedifferentiation process is relatively independent of the fat depot, obesity level, sex, or age of the cell donor [2]. The fibroblast-like cells resulting from the process have a great potential for proliferation [1].…”
Section: Introductionmentioning
confidence: 99%
“…Cells lose their round shape and become elongated as they shed their lipid content. At day 12 of the process, cells have a fibroblastic appearance (Figure 1) [2]. In addition to morphological changes, some authors observed important modifications in the expression of genes associated with the adipogenic and lipogenic programs of mature adipocytes in DFAT cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remodeling of the ECM has important effects on differentiation of preadipocytes and their ability to accumulate triglyceride lipid droplets (Chun, 2012), which indicates that the expression of MMPs could regulate the IMF by remodeling the ECM of preadipocytes and fibroblasts. Interestingly, MMP-1 has been reported as the most up-regulated MMP during the differentiation of cultivated adipocytes (Lessard et al, 2015). MMP-2-deficient mice were more resistant to high-fat diet-induced weight gain than littermate wild-type mice (Van Hul and Lijnen, 2008), which indicates that MMP-2 is essential to deposit lipids in the body.…”
Section: Relationships Of Mmp-1 -2 and -8 With Meat Quality Traitsmentioning
confidence: 99%